2018
DOI: 10.1002/jmv.25324
|View full text |Cite
|
Sign up to set email alerts
|

Mumps outbreak investigation in Jaisalmer, Rajasthan, India, June‐September 2016

Abstract: Mumps, a vaccine-preventable disease, cause inflammation of salivary glands and may cause severe complications, such as encephalitis, meningitis, deafness, and orchitis/oophoritis. In India, mumps vaccine is not included in the universal immunization program and during 2009 to 2014, 72 outbreaks with greater than 1500 cases were reported. In August 2016, a suspected mumps outbreak was reported in Jaisalmer block, Rajasthan. We investigated to confirm the etiology, describe the epidemiology, and recommend preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although many articles reporting MuV strains causing outbreaks in different individual countries were published in recent years (Braeye et al, 2014;Nedeljković et al, 2015;Park, 2015;Indenbaum et al, 2017;Willocks et al, 2017;Veneti et al, 2018;Moghe et al, 2019;el Zarif et al, 2020), studies at larger geographic scales are absent. The aim of the present study was to compare the circulation patterns of MuV in Spain and The Netherlands in a period of 5 years, as a step forward toward the study of broader patterns at European level.…”
Section: Introductionmentioning
confidence: 99%
“…Although many articles reporting MuV strains causing outbreaks in different individual countries were published in recent years (Braeye et al, 2014;Nedeljković et al, 2015;Park, 2015;Indenbaum et al, 2017;Willocks et al, 2017;Veneti et al, 2018;Moghe et al, 2019;el Zarif et al, 2020), studies at larger geographic scales are absent. The aim of the present study was to compare the circulation patterns of MuV in Spain and The Netherlands in a period of 5 years, as a step forward toward the study of broader patterns at European level.…”
Section: Introductionmentioning
confidence: 99%
“…Mumps incidence declined following widespread vaccination, and many developed countries have experienced a resurgence of mumps cases over the past decade. 2–4 There were 893 mumps outbreak cases reported between 1 March 2015 and 31 December 2016 among the highly vaccinated populations in northern Western Australia. 5 The surveillance data showed that mumps was one of the most common infectious diseases among children aged 0–14 years in Zhejiang Province in 2008–2017.…”
Section: Introductionmentioning
confidence: 99%